54 Effects of copper, zinc, and manganese source and concentration during late gestation on beef cow performance, fetal growth, and mineral status of cows and neonatal calves. (7th December 2018) - Stephenson, E; Rathert, A; Shoemake, B; Nagy, D; Messman, R; Freitas, T; Tucker, H; Meyer, A
Abstract: Multiparous, fall-calving, Sim-Angus cows (n = 48; 649 ± 80 kg BW; 5.3 ± 0.5 BCS; 4.3 ± 1.2 yr) were individually-fed tall fescue-based hay (12.2% CP, 61.5% NDF) and supplemented to meet/exceed nutrient recommendations except Cu, Zn, and Mn. From 91.2 ± 6.2 d pre-calving, cows received: no additional Cu, Zn, or Mn (CON); Cu, Zn, and Mn sulfates supplying 133% NASEM recommendations (ITM); Cu, Zn, and Mn metal methionine hydroxy analogue chelates (MMHAC, MINTREX®, Novus International) supplying 133% recommendations (CTM); or Cu, Zn, and Mn sulfates and MMHAC supplying 100% recommendations (reduce and replace, RR). Cows were pen-fed treatments in calving pens from 17.5 ± 8.0 d pre-calving to 11.0 ± 3.2 d post-calving. Data were analyzed with treatment and breeding group as fixed effects; sampling time was a repeated measure. Treatment did not affect ( P ≥ 0.28) cow pre-calving BW and BCS, calf birth BW and size, or placental mineral and size. Post-calving cow liver Cu was greater ( P ≤ 0.07) for CTM than other treatments. Calf liver Cu was greater ( P ≤ 0.06) for CTM than CON and for RR than ITM and CON. Calf liver Mn was less ( P ≤ 0.08) for RR than other treatments. Treatment did not affect ( P ≥ 0.17) cow or calf plasma Cu and Mn. Cow plasma Zn for RR was greater ( P ≤ 0.08) than CTM and ITM on d 28 and CTM and CON on d 56. At calving, ITM plasma Zn was greater ( P ≤ 0.10) than other treatments. Calf plasma Zn decreased ( P ≤ 0.01) from 0 (pre-suckling) to 48 h in CON and RR, but was unchanged ( P ≥ 0.48) in ITM and CTM. Data suggest late gestational Cu, Zn, and Mn supplementation improves liver Cu and plasma Zn in cows and calves.